Reinventing planning and planners: Ideological decontestations and rhetorical appeals. (February 2020) - Davoudi, Simin; Galland, Daniel; Stead, Dominic
This article contributes to the debate about ideologically motivated planning reforms. It aims to advance the debate by exploring how change is legitimised through forms of rhetorical persuasion. It shows how political ideologies become embedded in planning policies and practices through strategies of legitimation aimed at justifying specific ideas, beliefs and values as self-evident and inevitable. These legitimation strategies rely on distinctive rhetorical appeals to steer planning discourses, policies and institutions. By using short illustrative examples of 'ideology in action' from Britain, Denmark and the Netherlands, the article shows that various combinations of rhetorical appeals to logos, ethos, pathos and doxa (logic, character, emotion and identity) are often simultaneously at work to naturalise contested planning reforms.